PEMANFAATAN SERAT TANDAN KOSONG KELAPA SAWIT SEBAGAI PENGUAT PAPAN PARTIKEL DENGAN VARIASI FRAKSI VOLUME SERAT - Sunardi, Sunardi (Mesin, 2016)
Palm oil is a potential resource in Banten. The document by General Directory of Plantation Jakarta (201) showed that Lebak and Pandeglang produce 25.249 of palm oil with area 3,888 ha dan 2,907 ha, respectively.The other matter is production capacity of palm oil increase with environment problem. This research will discuss about using fiber from oil palmâs empty fruit bunch as reinforce material for composite. The preparation of particle board used cold press single punch method in compaction pressure 3 bars.The Sengon wood particle is used for filler and epoxy resin and PVAc as a matrix. Volume fraction of fiber is 5%, 10% and 15%, respectively. The characteristics of particle board are showed by density, thickness extending, hardness, impact and flexural strength. The result showed that particle board with 15% fiber is the best characteristic of the composite. The density, thickness extending, surface hardness, flexural strength and impact is0.973 g/cm3, 1.025%, 26 N/mm2, 14.484 N/mm2, and8,247 kJ/m2, respectively.Keyword: particle board, oil palmâs empty fruit bunch, mechanical properties, volume fraction